Implementation of sustainable innovation as sharia-based on the resto-pool development strategy of business - Dina Nur Wulandari; Muhammad Ahsan (JOURNAL OF SHARIA ECONOMICS, 2023)
Thesis with the title "Application of Sustainable Innovation as a Sharia-Based Resto-Karaoke Business Development Strategy (Comparative Study at the Muslim Generation Restaurant, Sumenep Madura and K-Broo True Family Karaoke Syariah Sidoarjo)". Aims to: Analyze the implementation of the Sharia-based restaurant-karaoke business concept at Resto Generasi Muslim in Sumenep and K-Broo True Family Karaoke Syariah in Sidoarjo. 2. Analyze the application of sustainable innovation at Resto Generasi Muslim in Sumenep and K-Broo True Family Karaoke Syariah in Sidoarjo. 3. Analyze the most effective business development strategies implemented in sustainable innovation to increase sales at Resto Generasi Muslim and K-Broo True Family Karaoke Syariah. This research utilizes a phenomenological approach and a qualitative comparative study. Data sources include primary data and secondary data obtained through observation, interviews, and documentation. Key informants include owners, managers, supervisors, employees, and customers of the Muslim Generation Resto in Sumenep and K-Broo True Family Karaoke Syariah in Sidoarjo. Data analysis is performed using techniques from Creswell.